Effect of core strengthening on dynamic balance and agility in badminton players - Sighamoney, R.; Kad, R.; Yeole, U. L. (International Journal of Physical Education, Sports and Health, 2018)
Background: Badminton is the most popular sport in world. However, badminton players require repetitive movements, like jumping, squatting, changing in position. This repetitive movement can affect lower limb injury. Balance is a major factor to prevent injury. Aim and Objectives: To find out the effect of core strengthening on dynamic balance and agility in badminton players. Methodology: 30 badminton players between the age 10-19 years (mean age14+) were selected and informed consent was taken. Subjects filled Questionnaire, and modified star excursion tests for dynamic balance and core strengthening program were done, data was collected and analysed & treated. Total 4 weeks 5 times in week of exercise protocol given. Modified star excursion scale used for dynamic balance pre and post of training period. Illinois t-test test used for assess the agility pre and post of training period. Result: The result showed that there is significant effect of core strengthening on dynamic balance and agility. The result showed increased distance in all three directions on modified star excursion scale and increased agility on t test. The p values of anterior, posteromedial, lateral distance are 0.0655, >0.10, >0.10 that is significant. The p value of agility score is 0.02 that is significant. Conclusion: There is effect of core strengthening on dynamic balance and agility in badminton players.